Developing nations paying for the sin of the rich - Abd Razak, Dzulkifli (2007)
LAST week was World Environment Day. Coming just a day before the start of the Group of Eight (G8) meeting (June 68) gave it a special significance. The meeting—held in Germany, the current European Union and G8 presidencies—had global warming and climate change high on its agenda. But not without great difficulty. Way before the meeting, US president George W Bush eagerly unveiled his plan for a "new" global framework to fight climate change, but many are sceptical. The US expects to set a longterm global goal for reducing greenhouse gases by the end of 2008 which is non-binding.